2020
DOI: 10.1212/cpj.0000000000000794
|View full text |Cite
|
Sign up to set email alerts
|

Neurology clinicians' views on palliative care communication

Abstract: BackgroundThe communication process of preparing patients and families facing progressive neurodegenerative diseases for future illness has not been empirically elucidated; the goal of this qualitative study was to explore neurology interdisciplinary health professionals' communication experiences, including current approaches, facilitators, and challenges.MethodsThree focus groups were conducted with 22 clinicians representing a range of health professions from several multidisciplinary neurology outpatient c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Communication agreements should be revisited and updated in response to patient needs, disease progression, and/or the cyclic decision‐making experienced by PwALS 78 . A formal communication agreement animates recommendations for individualized communication, 11,15,17,46 and a systematic, structured approach to communication 79 …”
Section: Discussionmentioning
confidence: 99%
“…Communication agreements should be revisited and updated in response to patient needs, disease progression, and/or the cyclic decision‐making experienced by PwALS 78 . A formal communication agreement animates recommendations for individualized communication, 11,15,17,46 and a systematic, structured approach to communication 79 …”
Section: Discussionmentioning
confidence: 99%
“…50 Communication challenges include when to begin goals of care discussions, how to support patients and caregivers during decision making, and how to increase familiarity with potential behavioral and communication problems in the future. 51…”
Section: Neuro-oncologymentioning
confidence: 99%
“…28 Recent research in neurology palliative care identified the need for a systematic approach to communication in neurodegenerative diseases including early discussions of goals and priorities to inform later decision making, preferably with caregivers present. 29 Using standardized language and documenting conversations were also recommended strategies. 29…”
Section: Improving Clinician-patient Communicationmentioning
confidence: 99%